Philosophical Discourses on Economic Governance: An African Perspectives - JACKSON, Emerson Abraham (Theoretical and Practical Research in Economic Fields, 2023)
This paper offers a comprehensive analysis of African perspectives on economic governance from a philosophical viewpoint. The study highlights the importance of incorporating African philosophical perspectives in economic governance and provides insights into the challenges and opportunities for economic governance in Africa. It also provides policymakers with valuable insights into the key factors that influence economic governance in Africa and highlights the necessary policy interventions required to improve economic governance in the region. Additionally, the study offers directions for future research, emphasizing the need for further research on the relationship between African philosophical perspectives and economic governance, as well as comparative studies of economic governance in different regions. Overall, this study contributes to the knowledge base on economic governance in Africa and provides important insights for policymakers and practitioners seeking to improve economic governance in the region .